Malignant Mesothelioma vs. Reactive Mesothelial Proliferations: Immunohistochemical Profile - Moretti, L. (2014)
AIMS: To examine the distribution of immunohistochemical markers GLUT-1, EMA (membrane epithelial antigen) and Ki-67 in benign and malignant mesothelial lesions. Thus, the sensitivity, specificity, positive and negative predictive value of these markers, used alone or in conjunction, was established. STUDY DESIGN: Observational, retro-prospective and non-randomized study. PLACE AND DURATION OF STUDY: Department of Pathology, Center for Medical Education and Clinical Research "Norberto Quirno" (CEMIC), between 2004 and 2011. METHODOLOGY: A total of 53 cases diagnosed as mesothelioma (n=15) or reactive mesothelial hyperplasia (n=38) were selected. Routine techniques using hematoxylin-eosin and immunostaining with EMA, GLUT-1, and Mib-1 were performed. RESULTS: Mesotheliomas cohort was immunoreactive for GLUT-1 in 11/15 (73%) cases, and for EMA in 13/15 (87%) cases. The group of reactive lesions was positive for GLUT-1 in 2/38 cases (5%), and positive for EMA in 7/38 (18%) cases. The median proliferation rate was 1% in benign lesions and 3% in mesotheliomas. The sensitivity and specificity for EMA was 87% and 82% respectively, with a positive predictive value of 65% and a negative predictive value of 94%. The sensitivity and specificity for GLUT-1 was 73% and 95% respectively, with a positive predictive value of 85% and a negative predictive value of 90%. CONCLUSION: EMA and GLUT-1 are sensitive and specific markers that express more frequently in mesothelioma than in benign mesothelial lesions with higher specificity in the case of GLUT-1 for the detection of malignant proliferations. In a mesothelial proliferation without invasion criteria, EMA and GLUT-1, including histopathology, may be sensitive and specific markers to define malignancy. Thus, a morphologically doubtful mesothelial proliferation with positive staining (diffuse and intense), for these antibodies could be a mesothelioma. However, the evidence of underlying tissue infiltration by mesothelial cells currently remains the gold standard for diagnosis of mesothelioma. Both markers should be included in the immunohistochemical panel to distinguish benign from malignant mesothelial lesions.